The dissonance of guilt : an examination of the human condition's fundamental dynamic of guilt feelings, referring to psychological and religious discourse and how they could be combined to facilitate mental health - Boothroyd, David Gordon (Department of Religious Studies, 2015)
Bibliography: leaves 187-208.